PENGARUH REMUNERASI DAN KOMUNIKASI TERHADAP MOTIVASI SERTA DAMPAKNYA PADA KINERJA PEGAWAI - Marhazni, Marhazni (Sosio Akademika, 2024)
Employee performance, both directly and indirectly, is determined by various internal and external factors. This study aims to analyze the effects of remuneration and communication on motivation and their impact on employee performance. A literature review shows that many studies exploring the relationship between remuneration, communication, motivation, and performance still reveal inconsistencies in results (research gap) and limitations regarding the context and approach used. Therefore, further research is important. The study was conducted at the Muaro Bungo District Attorney's Office, with 38 respondents, using a quantitative method. Data were collected through closed questionnaires and analyzed using path analysis techniques to test the relationships between variables. The research findings indicate that: remuneration and communication have a significant effect on motivation; communication and motivation have a significant effect on performance; while remuneration does not directly affect performance; remuneration and communication have an indirect impact on performance through motivation. These findings highlight the crucial role of communication in enhancing motivation and performance and show that, although remuneration does not directly influence performance, it still plays an important role in affecting performance through motivation. The implications of these empirical results suggest that organizations should focus on effective communication and adequate remuneration to enhance motivation, which in turn will positively affect performance. Another implication is that these empirical findings open up opportunities for further research in various organizational contexts, by expanding the analysis with additional variables that may influence this relationship, to gain a more comprehensive understanding.